'Not to escape the world but to join it': responding to climate change with imagination not fantasy. (13th June 2017) - Davison, Andrew
Abstract : The work of climate scientists, demonstrating human-driven climate change, has not provoked the widespread and far-reaching changes to human behaviour necessary to avert potentially catastrophic environmental trajectories. This work has not yet sufficiently been able to engage the individual and collective imagination. Drawing on Samuel Taylor Coleridge (1772–1834) and Iris Murdoch (1919–1999), we can distinguish two modes under which the human imagination can operate: in Murdoch's terms, these are 'imagination' and 'fantasy'. To relate imaginatively is to be willing to allow one's internal image of the world to be changed by what one encounters, while an outlook characterized by fantasy relates to the world as one would wish it were, rather than how it actually is. Fantasy, therefore, operates not only among those who deny climate change, but also among those who entertain the promise of a technological solution too optimistically. An imaginative outlook, by contrast, evaluates actions and patterns of behaviour in terms of their relation to a wider whole. This is necessary for providing the degree of agency required to step out of a cycle of ever accelerating production, which is explored in terms of an analogy to a discussion of revenge and forgiveness from Hannah Arendt (1906–1975). Ultimately, the need to engage the imagination is an opportunity as well as a challenge. To live imaginatively is fulfilling, and that is precisely what the challenges of climate change require. This article is part of the themed issue 'Material demand reduction'.